PENGARUH PERTUMBUHAN ASET DAN PERTUMBUHAN PENJUALAN TERHADAP RETURN SAHAM DENGAN RETURN ON ASEETS (ROA) SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN - Manul, Yustina Angela; Halim, Abdul; Sulistyo, Sulistyo (Jurnal Riset Mahasiswa Akuntansi, 2017)
Investment is one of the important means in improving the ability to collect and maintain wealth. One of the investment options that can be done is through stock investment in the capital market. Investor's expectation in investing is getting the profit level termed with stock return. Return is the goal of the investor to invest in the capital market. Investors perform various ways in order to get the desired return desired, by doing their own analysis on the trading behavior of a stock, or by using the means already provided from analysts in the capital market. The information that can be used as a benchmark of stock returns of companies studied is ROA, asset growth, and sales growth. This study aims to determine the effect of asset growth and sales growth on Stock Return through Return On Aseets (ROA) on manufacturing companies listed in Indonesia Stock Exchange (IDX) period 2015- 2016. This study using Simple random sampling is used to get the number of samples. Based on the technique, 36 companies were obtained as samples. Path analysis technique used in this research with the result that the higher level of ROA, asset growth, and sales growth hence the higher stock return also.